Thyroid Metastasis as First Manifestation of a Colon Adenocarcinoma With KRAS Mutation: Usefulness of 18F-FDG PET/CT. (October 2017) - Lecumberri, Beatriz; López, Elena; Coronado, Mónica; Rodado, Sonia; Castelo, Beatriz
Abstract : Abstract: The synchronous diagnosis of a thyroid metastasis and of the primary colon adenocarcinoma that produces it is very rare, with only 5 cases reported to date, all of them treated with thyroid surgery showing a mean survival of 7 months. An 18 F-FDG PET/CT in an asymptomatic 74-year-old woman with a thyroid cytology suggestive of malignancy but uncertain about the origin of the tumor revealed an stage IV colon adenocarcinoma with KRAS mutation and multiple metastasis (thyroid, lung, and liver). A prompt therapeutic planning with chemotherapy allowed 21 months of survival.